Biological and Social Economic Determinants of Adherence and Cure of Tuberculosis Treatment: Path Analysis Evidence from Yogyakarta - Tri Godha Fitriani; Setyo Sri Rahardjo; Hanung Prasetya (Masters Program in Public Health, 2019)
Background: Tuberculosis (TB) was an infectious disease which was still a health problem world